What Works in Therapeutic Prisons - Brown, J. author. aut Link
XX, 283 p.
Keywords: Exploring the first purpose-built prison community of its kind, the HMP Dovegate Therapeutic Community, this book provides the most comprehensive coverage of this research to date, following the progress of individual prisoners' through therapy and highlighting the key essentials for prisoners to address their motivations and criminal behaviour.